HSP90α lactylation orchestrates PGC1α and LRPGC1 nuclear translocation driving mitochondrial biogenesis - Gang Wu; Hongmin Li; Tong He; Min Chen; Xiaoyu Jiang; Mengli Wei; Lei Zhou; Chengyu Li; Jingli Tao; Zhaojun Liu; Ming Shen; Honglin Liu (Proceedings of the National Academy of Sciences, 2026)
Mitochondrial biogenesis is a fundamental process that ensures energy supply and supports steroidogenesis in ovarian cells. Lactate has recently been identified as a signaling metabolite that promotes mitochondrial biogenesis; however, the underlying regulatory mechanisms remain poorly defined. Here, we identify Heat Shock Protein 90 Alpha Family Class A Member 1 (HSP90α) lactylation as a key mediator that links glycolytic metabolism to mitochondrial function. Specifically, lactylation of HSP90α at K58 recruits ULK1, thereby enhancing phosphorylation at S39; lactylation at K616 prevents CDK5-mediated phosphorylation at S596. This dual regulation facilitates the nuclear translocation of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α) and its isoform LRPGC1, which activate NRF1/2-dependent transcription of mitochondrial biogenesis genes, such as Tfb1m , Tfb2m , and Tfam . Functionally, mitochondrial mass expansion both enhances cellular energy metabolism and promotes cholesterol import into mitochondria, thereby driving estrogen biosynthesis. Together, these findings reveal a lactate–HSP90α–PGC1α/LRPGC1 axis that metabolically couples glycolysis to mitochondrial biogenesis and reproductive hormone production, providing insights into the epigenetic regulation of follicular development.